2021
DOI: 10.3390/su13105580
|View full text |Cite
|
Sign up to set email alerts
|

Built Environment Factors Influencing Prevalence of Hypertension at Community Level in China: The Case of Wuhan

Abstract: This paper studies the correlation between built environment factors and the prevalence of hypertension in Wuhan, a typical city in central China. Data were obtained from a regional epidemiological database, which is the 2015 Epidemiological Survey of people under 65 years in 144 communities. The prevalence of hypertension was analyzed in five components based on the WHO framework (land use, transport, accessibility, green space, and socioeconomic status). Results indicated built environment factors have signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The increasing correlation between significant variables might decrease the value of ORs. Second, the great socioeconomic and environmental transformations related to hypertension during 2011-2018, such as dietary patterns, exposure to fine particulate matter (PM 2.5 ), built environment factors, and some other confounders, were not controlled in our study [ 52 - 54 ]. Third, the association of midday napping with hypertension might be moderated by other variables such as physical conditions and night sleep duration [ 49 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing correlation between significant variables might decrease the value of ORs. Second, the great socioeconomic and environmental transformations related to hypertension during 2011-2018, such as dietary patterns, exposure to fine particulate matter (PM 2.5 ), built environment factors, and some other confounders, were not controlled in our study [ 52 - 54 ]. Third, the association of midday napping with hypertension might be moderated by other variables such as physical conditions and night sleep duration [ 49 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another topic of general interest for Public Health is people's physical health, manifested through obesity, overweight and frailty, and generally calculated using the Body Mass Index (BMI) or Waist Circumference (WC) [67][68][69][70][71]. Other studies focus on the correlation between walkability and prevalence of diseases or health complications, such as cancer [72,73], hypertension [30,74], cardiovascular problems [29,75,76], diabetes [32] and dementia [31]. Other topics addressed under this subject include sedentarism [77][78][79] and overall well-being [80].…”
Section: Citation Analysismentioning
confidence: 99%
“…In this review, we found a total of 30 studies (47% of the sample) resorting to WS. In terms of countries where the WS was employed, 10 studies were done in the USA [29,38,67,73,86,[88][89][90]93,104], 8 in Japan [78,79,81,92,94,95,105,106], 3 in South Korea [34,82,91], 3 in Canada [65,66,107], and 2 in Australia [31,97], while the following countries have only one study that used WS: China [30], Germany [108], Italy [68], Spain [96], and Taiwan [109]. Regarding the most common research topics, in recent years WS was employed more commonly in Public Health [29][30][31][66][67][68]73,78,79,105,107,109,110] and Socio-economic and Demographics [88][89]…”
Section: Rq2: What Are the Most Used Walkability Indicators In Recent...mentioning
confidence: 99%
See 2 more Smart Citations